Pre-operative maintenance of angiotensin-converting enzyme inhibitors is not associated with acute kidney injury in cardiac surgery patients with cardio-pulmonary bypass: a propensity-matched multicentric analysis - Guilleminot, Pierre; Andrei, Stefan; Nguyen, Maxime; Abou-Arab, Osama; Besnier, Emmanuel; Bouhemad, Belaid; Guinot, Pierre-Grégoire; , Collaborator study group; Anciaux, Jean-Baptiste; Appriou, Annouck; Berthoud, Vivien; Bernard, Chloe; et al. (Frontiers in Pharmacology, 2024)
Objective: We investigated the effects of maintenance of angiotensin-converting-enzyme inhibitors (ACE-inhibitor) the day of the surgery on the incidence of postoperative acute kidney injury (AKI) and cardiac events in patients undergoing cardiac surgery.We performed a multicentric observational study with propensity matching on 1072 patients treated with ACE-inhibitors. We collected their baseline demographic data, comorbidities, operative and postoperative outcomes. AKI was defined by KDIGO (Kidney Disease: Improving Global Outcome).Results: Maintenance of ACE-inhibitor was not associated with increased risk of AKI (OR: 1.215 (CI95%:0.657-2.24)), p = 0.843, 71 patients (25.1%) vs 68 patients (24%)). Multivariate logistic regression and sensitive analysis did not demonstrate any association between ACE-inhibitor maintenance and AKI following cardiac surgery (OR: 1.03 (CI95%:0.81-1.3)). No statistically significant difference occurs in terms of incidence of cardiogenic shock (OR: 1.315 (CI95%:0.620-2.786)), stroke (OR: 3.313 (CI95%:0.356-27.523)), vasoplegia (OR: 0.741 (CI95%:0.419-1.319)), postoperative atrial fibrillation (OR: 1.710 (CI95%:0.936-3.122)), or mortality (OR: 2.989 (CI95%:0.343-26.034)). ICU and hospital length of stays did not differ (3 [2;5] vs 3 [2;5] days, p= 0.963 and 9.5 [8;12] vs 10 [8;14] days, p =0.638).Our study revealed that maintenance of ACE-inhibitors the day of the surgery was not associated with increased postoperative AKI. ACE-inhibitors maintenance was also not associated with increase rate of postoperative major cardiovascular events (arterial hypotension, vasopressors use, death).